Smart System for Real-time Monitoring of Vital Parameters - Bagín, Richard; Koteska, Bojana; Tysler, Milan; Ackovska, Nevena; Mishev, Anastas; Kostoska, Magdalena; Madevska Bogdanova, Ana (University of Novi Sad, Faculty of Sciences, Department of mathematics and informatics, Novi Sad, Serbia, 2024)
Wearable real-time systems that collect and intelligently analyze data on respiration, heart rate, oxygen saturation, blood pressure, and body temperature could assist medical personnel in selecting the most appropriate response during highly stressful situations in both military and civilian contexts, such as terrorist attacks, IED incidents, or rescue operations. These systems will issue an alert if there is a change in a person’s health status to prevent overlooking critical health changes. We propose designing and developing a prototype of a patch-like device and a methodology that enables the continuous monitoring of vital parameters of personnel or victims. The system involves using Artificial Intelligence to create software capable of real-time prediction of the parameters and alerting.
Keywords: vital parameters, emergency, biosensors, telemedicine; Smart Patch; medical systems